Long-term results of the European achalasia trial: a multicentre randomised controlled trial comparing pneumatic dilation versus laparoscopic Heller myotomy. Issue 5 (27th November 2015) - Moonen, An; Annese, Vito; Belmans, Ann; Bredenoord, Albert J; Bruley des Varannes, Stanislas; Costantini, Mario; Dousset, Bertrand; Elizalde, J I; Fumagalli, Uberto; Gaudric, Marianne; Merla, Antonio; Smout, Andre J; et al.
Abstract : Objective: Achalasia is a chronic motility disorder of the oesophagus for which laparoscopic Heller myotomy (LHM) and endoscopic pneumodilation (PD) are the most commonly used treatments. However, prospective data comparing their long-term efficacy is lacking. Design: 201 newly diagnosed patients with achalasia were randomly assigned to PD (n=96) or LHM (n=105). Before randomisation, symptoms were assessed using the Eckardt score, functional test were performed and quality of life was assessed. The primary outcome was therapeutic success (presence of Eckardt score ≤3) at the yearly follow-up assessment. The secondary outcomes included the need for re-treatment, lower oesophageal sphincter pressure, oesophageal emptying and the rate of complications. Results: In the full analysis set, there was no significant difference in success rate between the two treatments with 84% and 82% success after 5 years for LHM and PD, respectively (p=0.92, log-rank test). Similar results were obtained in the per-protocol analysis (5-year success rates: 82% for LHM vs 91% for PD, p=0.08, log-rank test). After 5 years, no differences in secondary outcome parameter were observed. Redilation was performed in 24 (25%) of PD patients. Five oesophageal perforations occurred during PD (5%) while 12 mucosal tears (11%) occurred during LHM. Conclusions: After at least 5 years of follow-up, PD and LHM have a comparable success rate with no differences in oesophageal function and emptying. However, 25% of PD patients require redilation during follow-up. Based on these data, we conclude that either treatment can be proposed as initial treatment for achalasia. Trial registration numbers: Netherlands trial register (NTR37) and Current Controlled Trials registry (ISRCTN56304564 ).